Rural GPs' attitudes toward participating in emergency medicine: a qualitative study - Magnus Hjortdahl; Peder Halvorsen; Mette Bech Risør (Taylor & Francis Group, 2016)
Objective: Health authorities want to increase general practitioner (GP) participation in emergency medicine, but the role of the GP in this context controversial. We explored GPs' attitudes toward emergency medicine and call outs. Design: Thematic analysis of focus group interviews. Setting: Four rural casualty clinics in Norway. Participants: GPs with experience ranging from one to 32 years. Results: The GPs felt that their role had changed from being the only provider of emergency care to being one of many. In particular, the emergency medical technician teams (EMT) have evolved and often manage well without a physician. Consequently, the GPs get less experience and feel more uncertain when encountering emergencies. Nevertheless, the GPs want to participate in call outs. They believed that their presence contributes to better patient care, and the community appreciates it. Taking part in call outs is seen as being vital to maintaining skills. The GPs had difficulties explaining how to decide whether to participate in call outs. Decisions were perceived as difficult due to insufficient information. The GPs assessed factors, such as distance from the patient and crowding at the casualty clinic, differently when discussing participation in call outs. Conclusion: Although their role may have changed, GPs argue that they still play a part in emergency medicine. The GPs claim that by participating in call outs, they maintain their skills and improve patient care, but further research is needed to help policy makers and clinicians decide when the presence of a GP really counts. Norwegian health authorities want to increase participation by general practitioners (GPs) in emergency medicine, but the role of the GP in this context is controversial.KEY POINTS The role of the GP has changed, but GPs argue that they still play an important role in emergency medicine. GPs believe that their presence on call outs improve patient care, but they find it defensible that patients are tended to by emergency medical technicians (EMTs) only. GPs offered different assessments regarding whether to participate in call outs in seemingly similar cases.